2016
DOI: 10.1016/j.hrthm.2015.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Procedural and biophysical indicators of durable pulmonary vein isolation during cryoballoon ablation of atrial fibrillation

Abstract: A time to effect of ≤60 seconds and an iTT0 of ≥10 seconds significantly predict PV isolation durability after the cryoballoon ablation of AF. If both criteria are met, the likelihood of PV reconnection may be exceedingly low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
161
4
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(182 citation statements)
references
References 13 publications
12
161
4
2
Order By: Relevance
“…The phase change is endothermic, causing the removal of heat from the target tissue (ie, the Joule‐Thomson effect) and finally resulting in a cryogenic lesion, as cells undergo necrosis and apoptosis 16 . This phenomenon on the cellular level has been then validated on the clinical one, as demonstrated by some studies which examined the relation between CbA‐NT and long‐term PVI durability 2,3,17 . Moreover, it has been proved that temperature drop during AF is faster and lower freezing values can be achieved in patients with ongoing AF during the procedure 18 .…”
Section: Discussionmentioning
confidence: 95%
“…The phase change is endothermic, causing the removal of heat from the target tissue (ie, the Joule‐Thomson effect) and finally resulting in a cryogenic lesion, as cells undergo necrosis and apoptosis 16 . This phenomenon on the cellular level has been then validated on the clinical one, as demonstrated by some studies which examined the relation between CbA‐NT and long‐term PVI durability 2,3,17 . Moreover, it has been proved that temperature drop during AF is faster and lower freezing values can be achieved in patients with ongoing AF during the procedure 18 .…”
Section: Discussionmentioning
confidence: 95%
“…Improved identification of PV potential disappearance has several potential clinical benefits. (1) Ineffective cryoballoon application can be stopped in cases of persistent LA–PV conduction continuing over 60 seconds of balloon freezing, because a time to PVI of ≤60 seconds significantly predicted PVI durability . (2) Time to PVI has been reported as a marker for the estimation of AF recurrence after cryoballoon PVI .…”
Section: Discussionmentioning
confidence: 99%
“…Next, the balloon was inflated and the balloon catheter was further advanced to the PV ostium as guided by the PV mapping catheter. After confirmation of PV occlusion by pulmonary venography, cryoablation commenced and continued for 180 seconds if confirmation of LA–PV disconnection or a PV temperature <−40°C could be achieved within the initial 60 seconds . If these were not achieved during the initial 60 seconds, we stopped the freezing and changed the positions of the PV mapping catheter and the balloon catheter in order to reocclude the PV.…”
Section: Methodsmentioning
confidence: 99%
“…While time to PV electrical isolation algorithms is now widely used to titrate the cryoapplication time it requires consistent PV potentials. Aryana et al reported that 81% of PVs sleeve potentials where recorded forcing the clinician to apply prolong freeze times to these veins. Furthermore, despite utilizing the time to isolation still, some of the cryoapplications fail to achieve long‐term PV isolation .…”
Section: Introductionmentioning
confidence: 99%
“…Aryana et al reported that 81% of PVs sleeve potentials where recorded forcing the clinician to apply prolong freeze times to these veins. Furthermore, despite utilizing the time to isolation still, some of the cryoapplications fail to achieve long‐term PV isolation . PV reconnection may reflect tissue stunning as a result of uneven ice formation .…”
Section: Introductionmentioning
confidence: 99%